Construction of RC pile for double storey semi-D houses / Nursyamimi Asyiqin Ahmad Nizam - Ahmad Nizam, Nursyamimi Asyiqin (Universiti Teknologi MARA, Perak, 2019)
Deep foundation is very important structure in the building. It role is to transmit load all the way from the roof to the firm layer underground. All the load such as live load, dead load and wind load will be transfer to the substructure. Ignoring the important of deep foundation may cause more costs for the remedial works in the future. Therefore, main purpose of deep foundation is to avoid structure from collapse or settlement. The objective of this report is to study the method of construction Reinforcement Concrete Pile. It also focuses on how to rectify problems occur during piling work. All the broken piles were rectified by adding more piles around the area to make sure the piles able to transmit load from structure. To sump up, the proper process of driven piling and welding joint between two piles is important to avoid any consequences such as broken pile.